Characterization of the tumor immune micromilieu and its interference with outcome after concurrent chemoradiation in patients with oropharyngeal carcinomas - Hess, Anne-Kathrin (Oncoimmunology, 2019)
Background: Intra-tumoral CD8 + T-cell infiltration in squamous cell carcinoma of the head and neck (HNSCC) has previously been linked to the efficacy of cisplatin-based chemoradiation (CDDP-CRTX) and immune checkpoint inhibitor (ICI) monotherapy. Further detailed characterization of the tumor immune-micromilieu and its influence on outcome may guide the development of CRTX-ICI combinations. Methods: Comprehensive immune transcriptome analysis was applied to a training set of tumor specimens from oropharyngeal squamous cell carcinoma (OPSCC) patients treated with CDDP-CRTX in the ARO-0401 phase III study (n = 33). A composite immune signature risk score (ISRS) for survival prediction was developed, and subsequently validated in two independent OPSCC cohorts treated with either CDDP-CRTX (n = 36) or mitomycin-based CRTX (MMC-CRTX, n = 31). Further validation of the ISRS was performed in the OPSCC subset (n = 79) of the TCGA HNSCC cohort. Potential interference between immune signatures and HPV status was evaluated in multivariate Cox regression models. Results: Significant differences according to the 3-y OS status in the abundance of tumor-infiltrating T- and B-cells, and the expression levels of 51 immune-related genes were observed. A risk score based on 13 differentially expressed genes involved in cytokine signaling, T-cell effector functions and the TNFR pathway was established as robust predictive factor of OS. Its predictive power was superior to the 6-gene interferon-gamma signature of ICI efficacy and independent of the HPV status. Conclusions: This study further elucidates the complex interaction of the tumor immune microenvironment with the efficacy of CDDP-CRTX in OPSCC. The results suggest immune markers for selection of patients treated with CRTX-ICI combinations.